One pot synthesis of Pt-doped CsxWO3 with improved near infrared shielding for energy-saving film applications. (15th January 2019) - Liu, Jingxiao; Ran, Shuai; Fan, Chuanyan; Qiao, Yuting; Shi, Fei; Yang, Jingyuan; Chen, Bin; Liu, Suhua
Graphical abstract: Highlights: Ptn -Csx WO3 were synthesized by one pot solvothermal method from cheap Na2 WO4 . Pt-doped Csx WO3 showed much higher infrared shielding rate than Csx WO3 . Pt-doping can catalyze enhancing the generation of W 5+ in Ptn -Csx WO3 particles. Ptn -Csx WO3 exhibited excellent properties without needing additional annealing. Pt0.01 -Csx WO3 sample exhibited best visible transparency and thermal insulation. Abstract: In this study, Pt-doped Csx WO3 (Ptn -Csx WO3 ) nanorods with improved near infrared shielding and transparent thermal insulation were synthesized by one pot solvothermal method using cheap sodium tungstate and cesium sulfate as raw materials. The role of Pt-doping on the crystal structure, morphology and transparent thermal insulation of the Ptn -Csx WO3 products was investigated. The results indicate that Pt catalysis plays an important role in promoting oxygen vacancies and W 5+ generation, and can improve the near infrared shielding performance of Ptn -Csx WO3 greatly. Furthermore, the as-synthesized Ptn -Csx WO3 nanorods could achieve excellent near infrared shielding and transparent thermal insulation performance without requiring additional reduction heat-treatment. Especially, when the Pt/W molar ratio is 0.01 (n = 0.01), the as-prepared Pt0.01 -Csx WO3 product with diameter of 10–30 nm and length of 20–80 nm exhibit best visible light transparency and near infrared shielding ability, with the maximum visible transmittance and near infrared shielding rate being 72% and 92% respectively. The excellent transparent thermal insulation performance of Ptn -Csx WO3 nanoparticles without needing additional heat-treatment enables them to be more suitable for energy-saving film applications in the building and automobile window glasses.